2021
DOI: 10.1111/gcb.15975
|View full text |Cite
|
Sign up to set email alerts
|

Data‐driven estimates of fertilizer‐induced soil NH3, NO and N2O emissions from croplands in China and their climate change impacts

Abstract: Gaseous reactive nitrogen (Nr) emissions from agricultural soils to the atmosphere constitute an integral part of global N cycle, directly or indirectly causing climate change impacts. The extensive use of N fertilizer in crop production will compromise our efforts to reduce agricultural Nr emissions in China. A national inventory of fertilizer N-induced gaseous Nr emissions from croplands in China remains to be developed to reveal its role in shaping climate change. Here we present a data-driven estimate of f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(36 citation statements)
references
References 55 publications
(88 reference statements)
2
33
1
Order By: Relevance
“…In our study, N 2 O-N and NO-N emission factors ranged from 0.21% to 0.57% and 0.09% to 0.21%, which was much lower than the latest results reported by Ma et al [8]. We speculated that this may be due to the lower production of N 2 O and the higher reduction ratio, resulting in a net reduction in N 2 O and NO emissions.…”
Section: 2contrasting
confidence: 82%
See 1 more Smart Citation
“…In our study, N 2 O-N and NO-N emission factors ranged from 0.21% to 0.57% and 0.09% to 0.21%, which was much lower than the latest results reported by Ma et al [8]. We speculated that this may be due to the lower production of N 2 O and the higher reduction ratio, resulting in a net reduction in N 2 O and NO emissions.…”
Section: 2contrasting
confidence: 82%
“…Previous studies indicated that excessive N input disrupted nutritional balance, and lowered soil pH, microbial activity, and diversity [5][6][7]. Furthermore, N fertilizer-induced soil nitrous oxide (N 2 O, a long-lived and potent greenhouse gas) and nitric oxide (NO, atmospheric photochemical pollutant) emissions have received widespread attention owing to the robust and steady rise of emission factors [8]. Therefore, the integrated improvement of N 2 O and NO mitigation while enhancing crop production and soil fertility should be implemented to promote sustainable agricultural development.…”
Section: Introductionmentioning
confidence: 99%
“…NO background emissions from tea plantations were significantly higher than those from vegetables (P < 0.01) but not different from those from orchards. Overall, we found that the magnitude of background emissions of gaseous reactive N was generally greater in Chinese OVT systems than in upland cereals [35] .…”
Section: Background Emissions and Fertilization-induced Gaseous N Emi...mentioning
confidence: 70%
“…The mean EF of N2O emission in Chinese orchards was 1.2% (range: 0.7%-1.72%), which was slightly lower than the world average of 1.4% (0.84%-1.86%) [20,25,37] . The mean EF of N2O emission from Chinese vegetable fields was 0.85% (0.55%-1.7%), and notably lower than the world average of 1.4% (0.93%-2.4%) [17,35,[38][39][40][41][42]44,45] . The EF of N2O in orchards and vegetables and its variability were comparable with the global mean (1%, range: 0.1%-1.8%) [48] .…”
Section: Efs Of Reactive Gaseous Nmentioning
confidence: 77%
“…Such EF d approaches are widely used to quantify not only N 2 O and NH 3 emissions from croplands across national and global scales (e.g., Cayuela et al, 2017; Aliyu et al, 2019; Yue et al, 2019; Ma et al, 2021a, b; Hergoualc’h et al, 2021), but also from cropland NO emissions at regional scale (e.g. Ma et al, 2021b; Yan et al, 2003). According to the Intergovernmental Panel on Climate Change (IPCC) Tier 1 guidelines, the EF d default value for NO is 0.70% for synthetic N fertilizer and manure (IPCC, 2006), though recently updated to 1.1% for synthetic N fertilizer (IPCC, 2019).…”
Section: Introductionmentioning
confidence: 99%